PERAN EKONOMI KREATIF DALAM MENINGKATKAN PEMBERDAYAAN SOSIAL KOMUNITAS LOKAL - Perlambang , Rizal; MS, Syaifullah; Thalib, Najdah; Santoso, Cahyo Budi; Prilosadoso, Basnendar Herry (JURNAL LENTERA BISNIS, 2025)
In the current era of globalization and digitalization, economic development does not only focus on the industrial and agricultural sectors, but also leads to the development of the creative economy sector. The creative economy, which is based on ideas, creativity and innovation, has become a new driving force in encouraging inclusive and sustainable economic growth. The aim of this research is to determine the role of the creative economy in increasing the social empowerment of local communities. The research uses a qualitative approach with a case study design. The analysis process includes coding data, identifying themes, and interpreting findings in the context of community empowerment through local skills. Triangulation of data sources and member check techniques are used to increase the credibility of research results. The results of this research found that the creative economy has a broad scope and a significant contribution to various aspects of the economy in Indonesia, especially in terms of increasing Gross Domestic Product (GDP), creating jobs, increasing tourism, and empowering local communities. In this section, we will discuss in more depth the role of creative economics in increasing the empowerment of local communities, its impact on job creation, its relationship with the tourism sector, as well as the opportunities and challenges faced by this sector in Indonesia.